2012
DOI: 10.2172/1047935
|View full text |Cite
|
Sign up to set email alerts
|

LIDAR Wind Speed Measurements of Evolving Wind Fields

Abstract: Light Detection and Ranging (LIDAR) systems are able to measure the speed of incoming wind before it interacts with a wind turbine rotor. These preview wind measurements can be used in feedforward control systems designed to reduce turbine loads. However, the degree to which such preview-based control techniques can reduce loads by reacting to turbulence depends on how accurately the incoming wind field can be measured. Past studies have assumed Taylor's frozen turbulence hypothesis, which implies that turbule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…The increasing need of monitoring the atmospheric boundary layer for a broad range of technological and scientific pursuits -such as for meteorology (Banta et al, 2002;Calhoun et al, 2006;Emeis et al, 2007;Horanyi et al, 2015;Vanderwende et al, 2015;Bonin et al, 2015), renewable energy (Thresher et al, 2008;Jones and Bouamane, 2011;Aitken et al, 2014;Iungo, 2016) and air traffic management (George and Yang, 2012;Smalikho and Banakh, 2015) -has led to a rapid development of remotesensing measurement techniques, such as wind lidars Cariou, 2015;Simley and Pao, 2012;Iungo andPorté-Agel, 2013, 2014) and radars (Farnet and Stevens, 1990;O'Hora and Bech, 2007;Hirth and Schroeder, 2013;Hirth et al, 2015). Compared to classical meteorological towers, remote-sensing instruments allow easier deployment, enhanced capability of varying deployment locations and potentially lower costs.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing need of monitoring the atmospheric boundary layer for a broad range of technological and scientific pursuits -such as for meteorology (Banta et al, 2002;Calhoun et al, 2006;Emeis et al, 2007;Horanyi et al, 2015;Vanderwende et al, 2015;Bonin et al, 2015), renewable energy (Thresher et al, 2008;Jones and Bouamane, 2011;Aitken et al, 2014;Iungo, 2016) and air traffic management (George and Yang, 2012;Smalikho and Banakh, 2015) -has led to a rapid development of remotesensing measurement techniques, such as wind lidars Cariou, 2015;Simley and Pao, 2012;Iungo andPorté-Agel, 2013, 2014) and radars (Farnet and Stevens, 1990;O'Hora and Bech, 2007;Hirth and Schroeder, 2013;Hirth et al, 2015). Compared to classical meteorological towers, remote-sensing instruments allow easier deployment, enhanced capability of varying deployment locations and potentially lower costs.…”
Section: Introductionmentioning
confidence: 99%
“…For both scenarios, the PSDs of the effective wind speeds at the turbine and the LIDAR measurements, as well as the CPSD between the two signals are calculated based on the spectral model of the wind field and the LIDAR and rotor properties using techniques outlined in [8] and [19]. The chosen preview distance of d = 90 m is near optimal for estimation of rotor effective wind speed, but is far from the optimal preview distance of d = 170 m found for estimating blade effective wind speed in [19].…”
Section: Minimum Mean Square Error Prefilter With Preview Constramentioning
confidence: 99%
“…Coherence is very high at low frequencies then decays to zero as frequency increases, mostly due to wind evolution, which causes higher frequencies of turbulence to decay more quickly than the low frequency structures. A detailed explanation of the sources of coherence loss is provided in [8].…”
Section: A Example 1: Rotor Effective Wind Speedmentioning
confidence: 99%
See 2 more Smart Citations